2014
DOI: 10.1002/cncr.29030
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of expectedness: Predictive accuracy of standard therapy outcomes in randomized phase 3 studies in epithelial ovarian cancer

Abstract: BACKGROUNDThe anticipated clinical outcome of the standard/control arm is an important parameter in the design of randomized phase 3 (RP3) trials to properly calculate sample size, power, and study duration. Changing patterns of care or variation in the study population enrolled may lead to a deviation from the initially anticipated outcome. The authors hypothesized that recent changes in patterns of care in epithelial ovarian cancer (EOC) have led to challenges in correctly estimating the outcome of control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The statistician takes comfort in the fact that by attaining the original number of target events specified in the design, power is maintained to detect the relative difference between the treatment arms whatever the underlying median time to outcome. Expanding on the point made by Castonguay et al 1 in Table 3 of their article, Table 1 presented herein shows how the absolute difference that can be detected with the stated study power varies as the median survival is underestimated by varying amounts; it also demonstrates how the power to detect the original target absolute difference declines. It should be emphasized that the power to detect the relative difference (specified in the hazard ratio) is maintained in all cases.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…The statistician takes comfort in the fact that by attaining the original number of target events specified in the design, power is maintained to detect the relative difference between the treatment arms whatever the underlying median time to outcome. Expanding on the point made by Castonguay et al 1 in Table 3 of their article, Table 1 presented herein shows how the absolute difference that can be detected with the stated study power varies as the median survival is underestimated by varying amounts; it also demonstrates how the power to detect the original target absolute difference declines. It should be emphasized that the power to detect the relative difference (specified in the hazard ratio) is maintained in all cases.…”
mentioning
confidence: 71%
“…The problems with underestimation that Castonguay et al 1 observed in studies with OS as the primary endpoint did not appear to the same extent in studies using PFS or TTP as a primary endpoint. The authors speculate as to the reasons for this in their article and, as they suggest, the introduction of more effective treatments and clinical management into second-line and subsequent treatment must be considered to play a role.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…This finding is particularly important given the large influence that parameter estimation has on sample size calculation and consequently on the reliability of the study outcomes. For example, the recent study by Castonguay et al reviewed the accuracy with which the median progression-free survival (PFS) and overall survival (OS) in the control arm had been estimated in studies of epithelial ovarian cancer between 2000 and 2010 (21). Their results highlight that PFS and OS of the control arm have frequently been underestimated, which means that the initial statistical assumptions of these trials may have been inaccurate.…”
Section: Discussionmentioning
confidence: 99%